2015
DOI: 10.1016/j.seizure.2015.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological and clinical findings on Nodding Syndrome in 21 South Sudanese children and a review of the literature

Abstract: This study confirms that NS is an encephalopathy and intellectual disabilities are partially independent of seizure frequency and EEG pathological activity. Based on interictal and ictal EEG patterns and on the experience of other researchers, valproic acid would seem to be the first-choice antiepileptic drug. NS in South Sudan presents with clinical and neurophysiological features which are similar to those described in northern Uganda and more severe than in Tanzania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 13 publications
5
22
1
Order By: Relevance
“…A high prevalence of epilepsy has been reported in many onchocerciasis meso- and hyper-endemic regions (>20% prevalence of onchocerca nodules) in Africa [[3], [4], [5], [6], [7], [8], [9], [10], [11]]. High numbers of persons with nodding syndrome (NS) and other forms of epilepsy have been reported in the Western Equatoria region of South Sudan [8,[12], [13], [14], [15], [16], [17]]. Since the first cases of NS were reported in 1990 in this region of South Sudan, a high rate of new NS cases and other forms of epilepsy have been reported [14].…”
Section: Introductionmentioning
confidence: 99%
“…A high prevalence of epilepsy has been reported in many onchocerciasis meso- and hyper-endemic regions (>20% prevalence of onchocerca nodules) in Africa [[3], [4], [5], [6], [7], [8], [9], [10], [11]]. High numbers of persons with nodding syndrome (NS) and other forms of epilepsy have been reported in the Western Equatoria region of South Sudan [8,[12], [13], [14], [15], [16], [17]]. Since the first cases of NS were reported in 1990 in this region of South Sudan, a high rate of new NS cases and other forms of epilepsy have been reported [14].…”
Section: Introductionmentioning
confidence: 99%
“…Nodding syndrome (NS) is a neurologic disorder of children in East Africa. NS is characterized by stereotypical head dropping movements, cognitive impairment, impaired growth, and seizures [ 2 , 4 , 5 , 7 , 16 , 19 , 23 , 24 ]. The age of onset is usually 5–15 years of age [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The age of onset is usually 5–15 years of age [ 5 ]. Although NS has been documented in the Republic of South Sudan [ 2 , 20 , 23 , 24 ] and Tanzania [ 19 ], it is currently a major health problem in the subsistence-farming villages of the Acholi people in northern Uganda [ 5 , 7 , 16 ]. NS emerged as an epidemic in the Kitgum district of Uganda in 1998 [ 5 , 11 ] during internal armed conflict and displacement of children into camps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…73 However, in 2015 de Polo and colleagues treated 21 patients with carbamazepine as a mono-or combination therapy and found that none obtained good control of any form of seizure associated with NS. 74 Benzodiazepines are indicated for icteric patients 5 , and given the symptomatic overlap between NS and catatonia, lorazepam has been piloted in NS patients. 75 Within one hour of lorazepam administration the severity of catatonia symptoms was reduced in 10/16 patients, and by more than 50% in six.…”
Section: Autoimmunitymentioning
confidence: 99%